2020
DOI: 10.1038/s41598-020-67410-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of long non-coding RNA (lncRNA) in the developing seeds of Jatropha curcas

Abstract: Long non-coding RNAs (lncRNAs) play critical roles in plant development. However, the information of lncRNAs in Jatropha curcas remains largely unexplored. Thus, an attempt has been made in J. curcas to identify 1,850 lncRNAs based on deep sequencing of developing seeds at three typical stages. About ten percent lncRNAs (196 lncRNAs) were differentially expressed lncRNAs during seed developing process. Together with reverse transcription quantitative real-time PCR, the lncRNA expression analyses revealed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…To better understand and clarify the response of lncRNA levels in axillary buds after topping, transcriptome sequencing and annotation were performed on both untopped and topped axillary buds. Most lncRNAs were < 1,000 nucleotides in length and contained only 1–2 exons, similar to the lncRNAs of other plants ( Yan et al, 2020 ; Huang et al, 2021 ). Some studies have found that the functions of lncRNAs are highly correlated with time.…”
Section: Discussionmentioning
confidence: 54%
“…To better understand and clarify the response of lncRNA levels in axillary buds after topping, transcriptome sequencing and annotation were performed on both untopped and topped axillary buds. Most lncRNAs were < 1,000 nucleotides in length and contained only 1–2 exons, similar to the lncRNAs of other plants ( Yan et al, 2020 ; Huang et al, 2021 ). Some studies have found that the functions of lncRNAs are highly correlated with time.…”
Section: Discussionmentioning
confidence: 54%
“…Various biological processes; development (from pollen to roots), reproduction (flowering/bolting), and stress responses are under the control of lncRNAs which indicate their fundamental regulatory roles [ 13 ]. Functional analysis of lncRNAs has also discovered the potential roles of lncRNAs in regulating the flowering/bolting time.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of sequencing technology, tens of thousands of lncRNAs have been identified. These lncRNAs participate in the regulation of different growth and development processes of plants, such as responses to pests and diseases [ 37 , 38 , 39 , 40 , 41 ], growth [ 42 , 43 , 44 ], and abiotic stresses [ 45 , 46 , 47 ].…”
Section: Production Characteristics Nomenclature and Classification O...mentioning
confidence: 99%